The Effects of Horizontal Merger Operating Efficiencies on Rivals, Customers, and Suppliers*. (29th May 2018) - Bernile, Gennaro; Lyandres, Evgeny
Abstract: We study how operating efficiencies in horizontal mergers affect market reactions of merging firms' rivals, customers, and suppliers. We measure operating efficiency gains using projections disclosed by merging firms' insiders. Higher efficiency gains are associated with lower announcement returns to merging firms' rivals (due to increased equilibrium output of merging firms), higher returns to their customers (due to lower equilibrium price of merging firms' output), and higher returns to their suppliers (due to the merged firm's higher equilibrium demand for inputs). Our results suggest that the pass-through of efficiency gains along merging firms' supply chains is as important as the effects of post-merger changes in market power.